Hyperammonemia and First-Degree Atrio-Ventricular Block in Adult Male from Valproic Acid Toxicity. (April 2023) - Wilson, Nicholas
Abstract: Introduction: The purpose of this case study is to review the clinical presentation and medical work of an adult male who experienced symptomatic hyperammonemia and first-degree atrio-ventricular block in the setting of valproic acid toxicity. Method: This case involves a 28-year-old African American male with a past psychiatric history of bipolar 1 disorder with psychotic features, antisocial personality disorder, PTSD, and ASD, who was psychiatrically hospitalized for mania and psychosis at a large midwestern university hospital. At the time of evaluation in the emergency department, the patient endorsed suicidal ideation, religious/persecutory delusions, and auditory hallucinations of demons. Zyprexa Zydis was started and titrated to 20 mg every 12 hours, which did not sufficiently improve symptoms. Depakote EC/DR 1000 mg every 12 hours was then added for treatment of mania. Approximately 1 week later, the patient was observed to be somnolent and complained of malaise, nausea, and vomiting. Results: Labs were collected which showed an elevated ammonia level of 336 umol/L and free valproic acid level of 13.3 mcg/ml. An EKG was performed which showed first-degree atrio-ventricular block with fusion complexes. The patient's baseline EKG displayed sinus bradycardia with no evidence of atrio-ventricular block. The patient's CMP was unremarkable except total bilirubin of 1.5 mg/dL and glucose of 104 mg/dL. His lactate was elevated at 1.95 mmol/L. The patient's troponin and CRP were unremarkable. The patient was medically transferred for management of hyperammonemia and EKG changes. Depakote was discontinued and lactulose 20 g TID was initiated. Patient was placed on telemetry and the first-degree atrio-ventricular block resolved within 24 hours after discontinuation of Depakote. Daily ammonia level, chem 7, and magnesium were collected. Ammonia decreased to 79 and 59 umol/L on consecutive days. Sodium was mildly elevated at 144 on day 2 of medical admission. Poison control was contacted and L-carnitine 990 TID was started for suspected carnitine deficiency. The patient medically recovered after several days and was readmitted to the psychiatric hospital for further psychiatric management. Conclusions: The patient's presentation of hyperammonemia and first-degree atrio-ventricular block were likely due to valproic acid toxicity. We suspect that carnitine deficiency contributed to the patient's valproic acid toxicity at lower-than-expected blood levels. Although antipsychotics can cause prolonged QTc interval, conduction disorders are not typical abnormalities. Caution should be taken when prescribing Depakote to individuals at higher risk of developing toxicity, including those with potential nutritional deficiencies as well as those with limited self-advocacy abilities secondary to psychiatric illness. Rapid identification of side effects, such as valproic acid toxicity, remain crucial for favorable patient outcomes. Funding: No Funding